On the Strength in Weakness: Human Figures Making History - Vansover, Yaron (Journal of Interdisciplinary Studies in Education, 2019)
A good story we have read or heard weaves a web of gossamer around us, linking us to it by five emotional reactions that it arouses. Most of these reactions are sparked by the characters in the story. To a great extent, they are responsible for creating interest in the story as a result of the human weaknesses they embody. Examining the historical story as told in the classroom space strangely reveals that this quality is lacking in its characters – the story lacks figures who have human weaknesses that might tie the students to it. The article calls on history teachers to enable these characters to enter the classroom and thus, to intensify the possibility that the students will like their history lessons.